The Isoperla of California (Plecoptera: Perlodidae); larval descriptions and a key to 17 western Nearctic species - Sandberg, John B. (Illiesia, 2011)
The male larvae of 17 western Nearctic species of the stonefly genus Isoperla Banks from California, Oregon, and Colorado were reared and confirmed study ingeverted male aedeagi. New maxilla characters are described for male larvae and used as primary characters in a larval species key. The larvae of two species, I. fulva Claassen and I. roguensis Szczytko & Stewart could not be separated and two species not currently known to occur in California, I. muir Szczytko & Stewart and I. tilasqua Szczytko & Stewart were included in the descriptions and key. Isoperla karuk Baumann & Lee is placed as a synonym of I. roguensis Szczytko & Stewart, and the larva of I. baumanni Szczytko & Stewart is correctly associated for the first time with the previously published description of I. bifurcata Szczytko & Stewart.
Keywords: entomologija; entomology; Plecoptera; vrbnice; stonefly; Isoperla; larval species key; maxillae; lacinia; western Nearctic; larve